1998
DOI: 10.1063/1.477182
|View full text |Cite
|
Sign up to set email alerts
|

A theory for compressible binary lattice polymers: Influence of chain conformational properties

Abstract: The influence of long-range chain connectivity on the thermodynamic properties of athermal compressible single component and binary polymer mixtures is studied for the lattice model both theoretically and by Monte Carlo simulations. Theoretical expressions for the thermodynamic properties are derived based on the chain insertion probabilities. The chain conformations enter the theoretical insertion probabilities by the number of intramolecular contacts. The distribution of the number of intramolecular contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…These values were obtained by assuming value of γ l = 0.22 (i.e., a lattice coordination number of 9), and calculating γ s by a fit to critical point data, Values of γ s between 0.25 and 0.30 were obtained, consistent with simulations, given the difference in lattice coordination number . Furthermore, it was pointed out to us by one of the reviewers of this paper that Wang et al also accounted for intramolecular contacts in polymer blends and derived equations that are essentially identical to ours (their derivation is far more rigorous, we might add). These authors also calculated the fraction of intramolecular contacts for chains of different lengths, obtaining results that are consistent with those we obtained.…”
Section: Conformational Contributions To Self-concentrationsupporting
confidence: 66%
“…These values were obtained by assuming value of γ l = 0.22 (i.e., a lattice coordination number of 9), and calculating γ s by a fit to critical point data, Values of γ s between 0.25 and 0.30 were obtained, consistent with simulations, given the difference in lattice coordination number . Furthermore, it was pointed out to us by one of the reviewers of this paper that Wang et al also accounted for intramolecular contacts in polymer blends and derived equations that are essentially identical to ours (their derivation is far more rigorous, we might add). These authors also calculated the fraction of intramolecular contacts for chains of different lengths, obtaining results that are consistent with those we obtained.…”
Section: Conformational Contributions To Self-concentrationsupporting
confidence: 66%
“…Freed and coworkers reported that the quasi-chemical theory of Guggenheim gives very good agreement with the simulation data [ 51 , 58 ]. For not too large interaction energies, the Guggenheim theory reduces to the Huggins approximation; hence, the Huggins theory is in this case also in very good agreement with these simulation data [ 51 , 58 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 54%
“…The density dependence of the chain conformations on the density has been investigated by Weinhold et al 92) and Wang et al 93) They derived the density dependence of the chain conformations due to the correlation between the intermolecular contacts and the extension of the chains. The comparison of their approach with Monte Carlo simulations exhibited reasonable agreement for short and intermediate chain lengths.…”
Section: X3mentioning
confidence: 99%
“…If the pure components exhibit a strong dependence of the density upon pressure and temperatures, this will also affect the conformations of the molecules and give rise to a composition dependence in a blend. The density dependence of the chain conformations on the density has been investigated by Weinhold et al 93 and Wang et al 94 . They derived the density dependence of the chain conformations due to the correlation between the intermolecular contacts and the extension of the chains.…”
Section: Single Chain Conformationsmentioning
confidence: 99%